Interconsulta dermatológica a receptores de transplante renal hospitalizados: um estudo observacional - Pereira, Amanda Regio [UNIFESP] (2017)
Background: Considering the rise in number and survival of solid organ transplant recipients (SOTR), there is a growing need for outpatient and inpatient services specialized in the care of these individuals. Dermatological abnormalities are highly prevalent in the hospital setting and can represent cutaneous findings of potentially severe systemic diseases, especially among immunocompromised patients. Literature about inpatient dermatology is scarce and no research was found concerning dermatology consultations specifically for SOTR. Objective: To evaluate the performance of dermatology consultation for renal transplant recipients (RTR) hospitalized in a Brazilian tertiary referral hospital for kidney transplantation (Hospital do Rim e Hipertensão – HRH). Methods: This is a clinical, observational, retrospective and descriptive study. All dermatology consultations performed at HRH for RTR over 36 consecutive months were included. Data were gathered from an electronic database and patient charts. Results: A total of 180 dermatology consultations were requested, 176 of these for a RTR. Four patients which were not RTR were excluded from the analysis. Male (64.2%) and young (average ± standard-deviation: 46.9 ± 15.6 years) patients predominated. In most cases, the dermatological complaint had arisen before admission (71.6%) and had been present for 30 days or less (59.7%). Infectious dermatoses motivated more than half of the consultations (52.3%), followed by inflammatory skin conditions (14.2%), neoplasms (12.5%) and drug reactions (8.5%). Herpes simplex, dermatophytosis and prurigo were the commonest diagnoses. There were some differences between ours and other studies from general hospitals, such as: the larger proportion of infectious dermatoses and neoplasms; the lower proportion of inflammatory diseases; the higher percentage of patients submitted to skin biopsy (40.3%); the lower proportion of consultations that were managed with a single visit (43.8%) and the higher probability of a systemic treatment being recommended (45.5%). There was diagnostic agreement between the requesting team and dermatologists in only 38.1% of the cases. Dermatology assessment changed the admission diagnosis in 11.4% of the consultations. Most of the requests were motivated by disorders of secondary relevance considering the main clinical scenario. However, the dermatology consultation was classified as extremely relevant or important in 75% of the cases. It was possible to manage skin conditions that are relatively uncommon in different settings, what highlights the educational potential of the consultations in this setting. Conclusion: Hospitalized RTR have specific dermatological demands and peculiarities when compared to general inpatients. It was observed a higher proportion of cases that demanded skin biopsy, systemic treatment for the dermatological condition and more than one visit to conclude dermatological evaluation. These findings possibly suggest a higher level of complexity in this sample. Different clinical and epidemiological presentations were also detected, such as the larger proportion of infectious dermatoses and cutaneous malignancies. Most of the consultations were motivated by common dermatologic conditions, not related to the admission diagnosis. However, the specificities of the inpatients, as well as the low proportion of diagnostic agreement between requesting and consulting teams, justify the need for dermatology consultation in high complexity hospitals, such as HRH.